2010
DOI: 10.1002/pi.2785
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and shape‐memory behavior of shape‐memory polymer composites with hybrid fillers

Abstract: Shape‐memory polymer (SMP) materials have several drawbacks such as low strength, low stiffness and natural insulating tendencies, which seriously limit their development and applications. Much effort has been made to improve their mechanical properties by adding particle or fiber fillers to reinforce the polymer matrix. However, this often leads to the mechanical properties being enhanced slightly, but the shape‐memory effect of reinforced SMP composites being drastically reduced. The experimental results rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…The utilization of electrically resistive Joule heating to drive SME is desirable and convenient to apply in a number of real-life applications, especially where direct heating is not easily achieved. A variety of conductive fillers from zero dimensional particles, one dimensional chains to two dimensional films, such as carbon nanotubes (CNTs) [22], carbon black [23], carbon nanofibers (CNFs) [24,25], magnetic particles [26], short carbon fibers [27,28], conductive alignment [29,30], CNF mat [31] and nanopaper [32] have been used in the SMP nanocomposites. These conductive fillers not only enable remote actuation of shape transitions but also enhance the thermal conductivity [33][34][35].…”
mentioning
confidence: 99%
“…The utilization of electrically resistive Joule heating to drive SME is desirable and convenient to apply in a number of real-life applications, especially where direct heating is not easily achieved. A variety of conductive fillers from zero dimensional particles, one dimensional chains to two dimensional films, such as carbon nanotubes (CNTs) [22], carbon black [23], carbon nanofibers (CNFs) [24,25], magnetic particles [26], short carbon fibers [27,28], conductive alignment [29,30], CNF mat [31] and nanopaper [32] have been used in the SMP nanocomposites. These conductive fillers not only enable remote actuation of shape transitions but also enhance the thermal conductivity [33][34][35].…”
mentioning
confidence: 99%
“…In 2007, Miaudet et al demonstrated broad glass transition temperatures as a result of incorporation of CNT fillers [21]. Further, in 2010, Lu et al modified a styrene-based shape memory polymer resin from the Ohio-based Cornerstone Research Group with carbon black fillers and carbon fiber fillers [22]. Nji and Li developed both a three-dimensional (3D) woven fabric reinforced SMP composite based on organic materials for impact resistance [23,24] and an SMP composite based on biomimicry.…”
Section: Smp-organic Compositesmentioning
confidence: 97%
“…Current efforts to implement this technology use conducting SMP composites with carbon nanotubes [7], short carbon fibers (SCFs) [8,9,12], and metallic Ni powder [10,11]. The shape memory effect in these types of SMPs have been shown to depend on the filler content, and they exhibit good energy conversion efficiency and improved mechanical properties.…”
Section: Function Of Cnf Paper In Shape Recovery Actuationmentioning
confidence: 99%
“…However, the actuation approach of shape recovery is seriously limited by traditional direct temperature heating procedures. Fortunately, many interesting and valuable studies have been done on the actuation of SMPs or SMP composites, for which shape recovery can not only be induced by external stimuli, such as heating, but can be manipulated by infrared light heating [5], laser light heating [6], electrical resistive heating [7][8][9][10][11][12][13], magnetic fields [14,15] or solvents [16][17][18].…”
Section: Introductionmentioning
confidence: 99%